Throwing Speed and Accuracy in Baseball and Cricket Players. Issue 3 (June 2014) - Freeston, Jonathan; Rooney, Kieron
Throwing speed and accuracy are both critical to sports performance but cannot be optimized simultaneously. This speed-accuracy trade-off (SATO) is evident across a number of throwing groups but remains poorly understood. The goal was to describe the SATO in baseball and cricket players and determine the speed that optimizes accuracy. 20 grade-level baseball and cricket players performed 10 throws at 80% and 100% of maximal throwing speed (MTS) toward a cricket stump. Baseball players then performed a further 10 throws at 70%, 80%, 90%, and 100% of MTS toward a circular target. Baseball players threw faster with greater accuracy than cricket players at both speeds. Both groups demonstrated a significant SATO as vertical error increased with increases in speed; the trade-off was worse for cricketers than baseball players. Accuracy was optimized at 70% of MTS for baseballers. Throwing athletes should decrease speed when accuracy is critical. Cricket players could adopt baseball-training practices to improve throwing performance.